HISTORY OF THE STUDY OF ANCIENT PROTECTIVE STRUCTURES OF THE FERGANA VALLEY (American Journal of Research in Humanities and Social Sciences, 2022)
This article describes the study of the protection of the Ferghana Valley based on historical sources.